ChemInform Abstract: A Matrix Isolation and Computational Study of Molecular Palladium Fluorides: Does PdF6 Exist?. Issue 14 (March 2016) - Wilson, Antony V.; Nguyen, Timothy; Brosi, Felix; Wang, Xuefeng; Andrews, Lester; Riedel, Sebastian; Bridgeman, Adam J.; Young, Nigel A.
Abstract: Binary palladium fluorides from PdF to PdF6 are investigated by matrix‐isolation methods using thermal evaporation and laser ablation to generate Pd atoms for reaction with F2 ‐doped Ar and Ne matrices as well as neat F2 matrices.